Cooperative sensitization on silver bromoiodide (AgBr/I) grains emulsion by oxalate and sulfur-plus-gold - Ma, Wang Jing (2013)
After sulfur-plus-gold sensitization on silver bromoiodide (AgBr/I) microcrystal emulsions prepared by the emulsifying process in the double-jet apparatus controlled by a microcomputer, a certain amount of oxalate salt (1×10-1、1×10-2、1×10-3and 1×10-4mol/molAg) was respectively added at a specific time and pAg to a reactor to prepare a series of tabular silver bromoiodide (AgBr/I) microcrystal at whose surface oxalate ions and Ag2S or AuAgS were doped. The sensitometric results from these crystal emulsions showed: 1) that the sensitivities of oxalate-doped AgBr/I emulsion, relative to that of the undoped emulsion as the controlled one, were remarkably increased; 2) that a cooperative sensitization by oxalate dopant, sulfur-plus-gold was observed without any significant increase in fog level when 10-3—10-4 mol/molAg oxalate was doped；3） that sensitivity gain (SG) was maximal, when 10-3mol/molAg oxalate (in 10-1—10-4 mol/molAg ) was doped at the surface of AgBr/I grains.